The influence of service quality and patients' emotions on satisfaction - Vinagre, H.; Neves, J. (International Journal of Health Care Quality Assurance, 2008)
Purpose – The purpose of this research is to develop and empirically test a model to examine the major factors affecting patients' satisfaction that depict and estimate the relationships between service quality, patient's emotions, expectations and involvement. Design/methodology/approach – The approach was tested using structural equation modeling, with a sample of 317 patients from six Portuguese public healthcare centres, using a revised SERVQUAL scale for service quality evaluation and an adapted DESII scale for assessing patient emotions. Findings – The scales used to evaluate service quality and emotional experience appears valid. The results support process complexity that leads to health service satisfaction, which involves diverse phenomena within the cognitive and emotional domain, revealing that all the predictors have a significant effect on satisfaction. Research limitations/implications – The emotions inventory, although showing good internal consistency, might be enlarged to other typologies in further research – needed to confirm these findings. Practical implications – Patient's satisfaction mechanisms are important for improving service quality. Originality/value – The research shows empirical evidence about the effect of both patient's emotions and service quality on satisfaction with healthcare services. Findings also provide a model that includes valid and reliable measures.